2017
DOI: 10.1186/s12864-017-3983-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the peripheral blood transcriptome and adaptive evolution of the MHC I and TLR gene families in the wolf (Canis lupus)

Abstract: BackgroundThe wolf (Canis lupus) is one of the most widely distributed terrestrial mammals, because it is well adapted to various ecological niches and their corresponding pathogen environments. Immunological competence is a crucial factor involved in adapting to a changing environment and fighting pathogen infection in animals. In this study, the peripheral blood transcriptome of wolves was generated via RNA-seq to advance understanding of the wolf immunome, with a special focus on the major histocompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 86 publications
(110 reference statements)
1
18
0
Order By: Relevance
“…A higher genetic diversity for TLR4 than for TLR7 has also been detected in a recent study across 23 rodent species (Fornůsková et al 2013 ), and similar results have been shown by Liu et al ( 2017 ) in wolves. Variation in TLR diversity is most likely a result of variable pathogen pressures.…”
Section: Discussionsupporting
confidence: 83%
“…A higher genetic diversity for TLR4 than for TLR7 has also been detected in a recent study across 23 rodent species (Fornůsková et al 2013 ), and similar results have been shown by Liu et al ( 2017 ) in wolves. Variation in TLR diversity is most likely a result of variable pathogen pressures.…”
Section: Discussionsupporting
confidence: 83%
“…The domestic dog has one classical MHCI gene with 73 alleles (Wagner et al 2002;Ross et al 2012;Venkataraman et al 2017); domestic cat has three classical MHCI genes (Yuhki et al 2008) with a number of alleles; and giant panda has four classical MHCI genes, of which Aime-I has 16 alleles (Pan et al 2008;Zhu et al 2013). Liu et al (2017) reported 17 functional alleles from four MHCI genes in four wolf (Canis lupus) individuals. Therefore, it is not surprising that we detected 7−19 PFAs in the four Meles species (Supplementary Tables S2-S5).…”
Section: Discussionmentioning
confidence: 99%
“…The number of MHCI genes identified to date in eutherian mammals varies from species to species, ranging from 51 genes in the rhesus macaque (Shiina et al, ) to seven in the domestic dog (Yuhki et al, ). The number of functional MHCI genes ranges from about four in the domestic dog to 30 in the rhesus macaque (Liu et al, ; Shiina et al, ; Yuhki et al, ). The numbers of both MHCI genes and PFGs identified in most species in our study (Table ) were well within these ranges, although the killer whale and pangolin were exceptions.…”
Section: Discussionmentioning
confidence: 99%